233k views
1 vote
The function f(x)= -x^2+2x+6

User Rzlvmp
by
5.3k points

2 Answers

2 votes

Answer:

See below

Explanation:

X-intercepts / Zeroes / Roots:


f(x)=-x^2+2x+6


0=-x^2+2x+6


x=(-b\pm√(b^2-4ac))/(2a)


x=(-2\pm√(2^2-4(-1)(6)))/(2(-1))


x=(-2\pm√(4+24))/(-2)


x=(-2\pm√(28))/(-2)


x=(-2\pm2√(7))/(-2)


x=1\pm√(7)


(1+√(7),0) and
(1-√(7),0)

Y-intercept:


f(x)=-x^2+2x+6


f(0)=-(0)^2+2(0)+6


f(0)=6


(0,6)

Vertex:


x=-(b)/(2a)


x=-(2)/(2(-1))


x=(-2)/(-2)


x=1


f(1)=-(1)^2+2(1)+6


f(1)=-1+2+6


f(1)=1+6


f(1)=7


(1,7)

Domain:


(-\infty,\infty)

Range:


(\infty,7)

User Guiyo
by
5.3k points
4 votes

Answer:

is a function

Explanation:

the x coordinate do not repeat themselves

User Cayce K
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.